Muscle ultrasonography in detecting fasciculations: A noninvasive diagnostic tool for amyotrophic lateral sclerosis. Issue 2 (15th October 2021) - Rajula, Rahul Reddy; Saini, Jitender; Unnikrishnan, Gopikrishnan; Vengalil, Seena; Nashi, Saraswati; Bardhan, Mainak; Huddar, Akshata; Chawla, Tanushree; Sindhu, Dodmalur Malikarjuna; Ganaraja, Valakunja Harikrishna; Polavarapu, Kiran; Preethish‐Kumar, Veeramani; et al.
Abstract: Background and objectives: Muscle ultrasound (MUS) is an emerging noninvasive tool to identify fasciculations in amyotrophic lateral sclerosis (ALS). We assessed the utility of MUS in detecting fasciculations in suspected ALS patients. Methods: Thirty‐three patients (25 men) with possible ( n = 7), probable ( n = 12), or definite ALS according to Awaji criteria were studied. Electromyography was done in biceps brachii, quadriceps, and thoracic paraspinal muscles and MUS in biceps, triceps, deltoid, abductor‐digiti‐minimi, quadriceps, hamstrings, tibialis anterior, thoracic paraspinal, and tongue muscles. Results: The age at onset and illness duration was 49.73 ± 12.7 years and 13.57 ± 9.7 months, respectively. Limb‐onset = 24 patients (72.7%) and bulbar‐onset = 9 (27.3%). Totally 561 muscles were examined by MUS. Fasciculations were detected in 84.3% of muscles, 98.4% with and 73% without clinical fasciculations ( p < 0.001). Fasciculation detection rate (FDR) by MUS was significantly higher in muscles with wasting (95.6%) than without wasting (77.6%, p < 0.001). Compared with EMG, FDR was significantly higher with MUS in quadriceps (81.8% vs. 51.5%, p = 0.002) and thoracic paraspinal muscles (75.8% vs. 42.4%, p = 0.013). The proportion of patients with definite ALS increased from 42% by clinical examination to 70% after combining EMG and MUS findings. Conclusions: MUS is more sensitive in detecting fasciculations than electromyography (EMG) and provides a safer, faster, painless, and noninvasive alternative to EMG in detecting fasciculations in ALS. Abstract : Fasciculation detection rate in the various muscles sampled by muscle ultrasound. ADM, abductor digiti minimi